GENOTYPIC VARIATIONS FOR SALINE TOLERANCE IN MORUS SPECIES BASED ON THEIR OVERALL ATTRIBUTES - M.GNANARAJ; O.SIVAKUMAR; R. NOBEL SURYA PANDIDURAI (International Journal of Pharma and Bio Sciences, 2011)
A study to determine the nutritive value of mulberry (Morus sps.,) leaves, under the saline stress condition was conducted. Here four major saline tolerant genotypes of mulberry (S1635, S36, S13, and MR2) were taken for the test, and their nutritional values were estimated. Among the four saline tolerant genotypes of mulberry S-1635 suggested as a best genotypic variety because S-1635 has high nutritive value compared with the other 3 genotypes, also its growth and yield parameters is more convenient compared with other types. So, under the saline stress S-1635 gives good yield and also recommended as a best genotypic feed with high nutritive value for the Silkworm. The genotypes are recommended as follows based on their nutritive values, S1635, MR2, S36, and S13.